Laccase Enzyme Electrode with Ferrocene-Monocarboxylic Acid Mediator for Determination of Phenol - MUCHINDU, M.; NGILA, J.C. (Asian Journal of Chemistry, 2010)
Laccase biosensor with ferrocene-based mediator for determination of phenol using voltammetry is discussed. Phenols are major constituents of several industrial effluents. Phenols were first isolated from coal tar and occur widely in nature particularly in protein-containing materials. Phenols are toxic to fish at levels above 2 μg/L and fatal in humans at 1 μg/L. Thus discharge of phenolic compounds into the environment is hazardous as they have the potential to contaminate superficial and underground water. Laccase oxidizes many different substrates including ortho- and para-substituted mono- and polyphenols, polyamines, lignins and aryl diamines as well as arscobate ion. Laccase is not a very strong oxidant and in some cases requires electron transfer mediators. Ferrocene monocarboxylic acid (Fc-COOH) was used as an electron transfer mediator for laccase. Thus a mixture of laccase enzyme and ferrocene monocarboxylic acid dissolved in phosphate buffer (pH 6.5), at a glassy carbon working electrode, was used as a biosensor for detection of phenol. The laccase biosensor was applied in wastewater samples collected from industrial effluents of coal-based power generation and coal mining plants. The results obtained show that the laccase electrode is suitable for determination of trace amounts of phenols at picomolar (pM) levels. Detection limit of 1.0 pM, linear range 0.5-100 pM and sensitivity of 0.2 μA/pM, were obtained. The coal-based effluent sample was found to contain an average of 47.7 pM of phenol.